2021
DOI: 10.1186/s12862-021-01779-9
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in morphology, gene expression, and selection underlie web loss in Hawaiian Tetragnatha spiders

Abstract: Background A striking aspect of evolution is that it often converges on similar trajectories. Evolutionary convergence can occur in deep time or over short time scales, and is associated with the imposition of similar selective pressures. Repeated convergent events provide a framework to infer the genetic basis of adaptive traits. The current study examines the genetic basis of secondary web loss within web-building spiders (Araneoidea). Specifically, we use a lineage of spiders in the genus Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 93 publications
0
7
0
Order By: Relevance
“…In addition to fibroins, there are several other proteins found in both moths and caddisflies. Zons have been commonly found in silk throughout the order Lepidoptera ( Zhang et al, 2015 ; Zurovec et al, 2016 ; Kludkiewicz et al, 2019 ; Rindos et al, 2021 ; Rouhova et al, 2021 ), and homologous transcripts have also been detected in spider silk glands ( Berger et al, 2021 ). However, our previous study in T. bisselliella showed that they are mainly expressed in the MSG ( Rouhova et al, 2021 ), whereas in P. conspersa , we detected their transcripts in the posterior part of SGs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to fibroins, there are several other proteins found in both moths and caddisflies. Zons have been commonly found in silk throughout the order Lepidoptera ( Zhang et al, 2015 ; Zurovec et al, 2016 ; Kludkiewicz et al, 2019 ; Rindos et al, 2021 ; Rouhova et al, 2021 ), and homologous transcripts have also been detected in spider silk glands ( Berger et al, 2021 ). However, our previous study in T. bisselliella showed that they are mainly expressed in the MSG ( Rouhova et al, 2021 ), whereas in P. conspersa , we detected their transcripts in the posterior part of SGs.…”
Section: Discussionmentioning
confidence: 99%
“…Some have adopted a web‐less, active hunter or cursorial lifestyle (e.g. Berger et al., 2021). Some tetragnathid genera such as Tetragnatha are secondarily‐haplogyne whereas most of them have entelegyne genitalia (Griswold et al., 1998; Álvarez‐Padilla & Hormiga, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…2018 ). Moreover, comparison with the closely related Hawaiian T. kauaiensis will provide insights into the loss of web-building behaviors and the loss of an obligate association with water that characterize many of the Hawaiian Tetragnatha including T. kauaiensis ( Berger et al . 2021 ).…”
Section: Discussionmentioning
confidence: 99%